(untitled) (Eurasian Journal of Ecology, 2022)
The article analyzes the monitoring of hydrogen sulfide content in the air of Atyrau in the winter period of 2021-2022. The purpose of this study is to study the hydrogen sulfide content in the air environment of the city of Atyrau, which has been increasing in recent years as a result of anthropogenic impact. The monitoring results were analyzed according to the data of Kazhydromet observation points, including 15 observation points. Monitoring of the study showed that among 15 observation points, there are exceedances of the maximum permissible concentrations of hydrogen sulfide in all three winter months, but however, it can be observed that the highest concentrations are observed in December and February, whereas in January these data are close to the MPC. Especially high rates are characteristic of points located near the Atyrau Oil Refiner, which is probably the main source of hydrogen sulfide. At the same time, the excess of the MPC for hydrogen sulfide and at points in the territories of the city exceeds more than 5-15 times. An important step towards optimizing the monitoring of the effects of hydrogen sulfide emissions at the Atyrau Refinery is the monitoring of atmospheric air quality and the introduction of modern technologies and dust and gas cleaning equipment. At the same time, it is possible to reduce the emission of hydrogen sulfide as a result of measures aimed at the reconstruction and overhaul of the sewage system in Atyrau. Key words: hydrogen sulfide in the air, Atyrau, monitoring, winter period, Kazhydromet observation points.